2020
DOI: 10.1590/1808-1657000352019
|View full text |Cite
|
Sign up to set email alerts
|

Biological parameters of Spodoptera cosmioides Walker (Lepidoptera: Noctuidae) in cotton varieties

Abstract: Spodoptera cosmioides Walker is a polyphagous insecticide-resistant species found in various regions of Brazil. Despite occurring at low densities, it is considered a potential pest of cotton, soybean, and bean crops in the Brazilian cerrado. This work investigated the comparative biology of S. cosmioides in the commercial transgenic cotton NuOPAL (Bollgard I, Evento 531) and the conventional isoline variety DeltaOPAL. The experiment was conducted under laboratory conditions (26 ± 1°C; relative humidity: 70 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Similar results were observed for S. eridania fed on Cry1Ac/Cry1F‐cotton 30 . Previous studies also reported that S. eridania and S. cosmioides had naturally low susceptibility to Cry1Ac and Cry1F proteins in diet bioassays 13,31–34 and to Cry1Ac‐soybean 13,35 and Cry1Ac‐cotton 36,37 . Consistent with these findings, other species from the Spodoptera genus including S. frugiperda , S. exigua (Hübner) and S. litura (F.) exhibited low susceptibility to Cry1Ac‐soybean, 13,37 Cry1Ac‐cotton 24,25,38,39 and Cry1Ac/Cry1F‐cotton 24,26 .…”
Section: Discussionsupporting
confidence: 71%
“…Similar results were observed for S. eridania fed on Cry1Ac/Cry1F‐cotton 30 . Previous studies also reported that S. eridania and S. cosmioides had naturally low susceptibility to Cry1Ac and Cry1F proteins in diet bioassays 13,31–34 and to Cry1Ac‐soybean 13,35 and Cry1Ac‐cotton 36,37 . Consistent with these findings, other species from the Spodoptera genus including S. frugiperda , S. exigua (Hübner) and S. litura (F.) exhibited low susceptibility to Cry1Ac‐soybean, 13,37 Cry1Ac‐cotton 24,25,38,39 and Cry1Ac/Cry1F‐cotton 24,26 .…”
Section: Discussionsupporting
confidence: 71%
“…42 It is an important cotton pest, and biotechnology for its control has been developed: the use of Cry toxins of Bacillus thuringiensis (Bt) (Berliner, 1915) in transgenic or biological control. 8 For the infested G. hirsutum plants, otherwise, both younger and older leaves presented equivalent total phenolic levels, as the young non-infested leaf. Therefore, the physiological response to the loss of leaf area fed by S. cosmioides caused a reduction in the Table II.…”
Section: Discussionmentioning
confidence: 95%
“…7 Spodoptera cosmioides (Walker) (Lepidoptera, Noctuidae) caterpillars are polyphagous, causing damage to cotton, soybean maize, and other crops. 8 Plant secondary metabolites comprise more than 100.000 substances that may have applications such as pharmaceuticals, insecticides, dyes, flavors, and fragrances. 9 Secondary metabolites may be induced by pests that become more tolerant to new infestations.…”
mentioning
confidence: 99%